Vpogled v izhodišča za Dialoge Primoža Kozaka - Voglar, Dušan (Slavistična revija, 2010)
Primož Kozak's play Dialogi reveals through the dialogues between four intellectuals four conflicting models of existence of an individual in a post-revolutionary world. Philosophical and ethnical origins of the play are presented partially in Kozak's essays, partially in the sources previously not considered (fiction, mostly not published until 2005; manuscript notes).
Keywords: družbene razmere; Kozak, Primož, 1929-1981; Kozak, Primož: Dialogi; literarne študije; Slovene literature; slovenska dramatika; slovenska književnost